The Academy and the Award : The Coming of Age of Oscar and the Academy of Motion Picture Arts and Sciences - Davis, Bruce (Former Executive Director of the Academy of Motion Picture Arts and Sciences), 1943- (Book collections on Project MUSE., 2022)
"The early history of the formation of the Academy of Motion Picture Arts and Sciences and its most famous award-the Oscar-as told by its former executive director who reveals many previously unknown stories"--